Silicon-carbon negative electrode material with low expansion rate as well as preparation method and application of silicon-carbon negative electrode material
By using a low expansion rate silicon-carbon anode material preparation method in lithium-ion batteries, ultrasonic dispersion and mechanical stirring are used to form a silicon/carbon composite material, and the volume expansion of traditional anode material is solved through carbon coating and chitin addition steps such as carbon coating, and the addition of chitin. The problems of large rate and poor circulation capacity have improved the performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411257051.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The volume expansion rate of the negative electrode material of traditional lithium-ion batteries is relatively large and the circulation capacity is poor, which cannot meet the energy density and cycle life requirements of modern equipment.
A method of preparing silicon carbon negative electrode material with low expansion rate is adopted. The amorphous silicon, acetylene black and tin oxide are uniformly dispersed in a glycerol solution through ultrasonic dispersion and mechanical stirring, and then hydrothermal reaction is carried out in an electric-thermal constant temperature drying box. , a silicon/carbon composite material is formed, and carbon coated by chemical vapor deposition method, and finally chitin and vinyl carbonate are added to form a silicon carbon anode material with low expansion.
It significantly improves the performance of lithium-ion batteries, including the first-round charging specific capacity and cycle stability, reduces the capacity attenuation rate, and meets the energy density and cycle life requirements of modern lithium-ion batteries.
Smart Images

Figure BDA0005034409320000081 
Figure BDA0005034409320000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of silicon-carbon negative electrode materials, and in particular to a silicon-carbon negative electrode material with a low expansion rate, and a preparation method and application thereof. Background Art
[0002] With the rapid development of electric vehicles, mobile devices and other fields, the demand for lithium-ion batteries continues to increase. However, traditional lithium-ion battery negative electrode materials, such as graphite, can no longer meet the energy density and cycle life requirements of modern devices due to their low specific capacity and high volume expansion rate. Therefore, there is an urgent need for a silicon-carbon negative electrode material with a low expansion rate and its preparation method and application. Summary of the invention
[0003] The purpose of the present application is to provide a silicon-carbon negative electrode material with a low expansion rate and a preparation method and application thereof, so as to solve the problem that the negative electrode material in the prior art has a large volume expansion rate and poor cycle capacity.
[0004] The present application provides a method for preparing a silicon-carbon negative electrode material with a low expansion rate, comprising the following steps: S1, preparing a silicon-carbon composite material: mixing amorphous silicon and acetylene black in a glycerol solution, then adding tin oxide, and obtaining a tin oxide-amorphous silicon-acetylene black mixture after ultrasonic dispersion, adding a polyvinyl pyrrolidone solution to the obtained tin oxide-amorphous silicon-acetylene black mixture, mechanically stirring it evenly, and performing a hydrothermal reaction at a constant temperature in an electric constant temperature drying oven, evaporating the glycerol solvent, and grinding to obtain a silicon / carbon composite material.
[0005] S2, adding chitosan to the silicon / carbon composite material obtained in step S1, mixing evenly, cooling the mixture, and then adding ethylene carbonate to gradually solidify the mixture to obtain a silicon-carbon negative electrode precursor material;
[0006] S3, carbon-coating the silicon-carbon negative electrode precursor material obtained in step S2 by chemical vapor deposition to obtain a carbon-coated silicon-carbon negative electrode material.
[0007] Preferably, in step S1, the mass ratio of amorphous silicon to acetylene black is 8:2, the amount of tin oxide added is 8% of the total mass of amorphous silicon and acetylene black, the amount of polyvinyl pyrrolidone added is 5% of the mass of the tin oxide-amorphous silicon-acetylene black mixture, and the mass of the glycerol solution is 10 times the total mass of amorphous silicon and acetylene black.
[0008] Preferably, in step S2, the mass ratio of the silicon / carbon composite material to chitosan is 10:3, and the amount of ethylene carbonate added is 15% of the total mass of the silicon / carbon composite material and chitosan.
[0009] Preferably, in step S1, the mechanical stirring time is 2 hours, the mechanical stirring speed is 1000 rpm, the temperature of the electric thermostat is 80° C., and the hydrothermal reaction time is 3 hours.
[0010] Preferably, in step S1, evaporating the glycerol solvent is performed in an oven at a temperature of 90° C. for 4 hours.
[0011] Preferably, in step S2, before adding chitosan to the silicon / carbon composite material obtained in step S1 and mixing them evenly, the chitosan is dried in an oven and then ground to a particle size of 50 mesh.
[0012] Preferably, in step S2, the cooling rate is 5°C / min, and the temperature is cooled to 10°C.
[0013] Preferably, in step S3, the temperature of carbon coating is 850-900°C, the gas source used is acetylene, methane, liquefied gas or gaseous carbon source, and the duration is 1 hour.
[0014] The present application provides a silicon-carbon negative electrode material obtained according to the preparation method of the above-mentioned silicon-carbon negative electrode material with low expansion rate.
[0015] The present application provides an application of a silicon-carbon negative electrode material obtained according to the preparation method of the above-mentioned silicon-carbon negative electrode material with a low expansion rate in a lithium battery.
[0016] Therefore, the present application adopts the above-mentioned low expansion rate silicon-carbon negative electrode material and its preparation method and application, which has the following beneficial effects:
[0017] (1) Amorphous silicon, doped heteroatom materials and acetylene black can be effectively dispersed in the propylene glycol solution by ultrasonic dispersion and mechanical stirring, which improves the uniformity of the mixture and is beneficial to the bulk doping of silicon-carbon negative electrode materials, thereby improving the overall performance of the material.
[0018] (2) The addition of chitosan may form a certain pore structure in the silicon-carbon composite material, which helps to increase the specific surface area of the material and thus improve its electrochemical performance.
[0019] (3) The present application significantly improves the performance of the battery by adjusting the ratio between the various raw materials. DETAILED DESCRIPTION
[0020] Example 1
[0021] First, amorphous silicon powder and acetylene black are mixed in a ratio of 8:2, and then added to a glycerol solution (the mass of the glycerol solution is about 10 times the total mass of amorphous silicon and acetylene black), and then tin oxide is added, the amount of tin oxide added is 8% of the total mass of amorphous silicon and acetylene black, and ultrasonic dispersion is performed by an ultrasonic disperser for 10 minutes. After ultrasonic dispersion, a tin oxide-amorphous silicon-acetylene black mixture is obtained, and the tin oxide-amorphous silicon-acetylene black mixture is transferred to a magnetic stirrer, polyvinyl pyrrolidone is added, and mechanical stirring is performed, the stirring speed is set to 1000rpm, and the stirring time is about 2 hours, until the mixture becomes viscous. Then it is transferred to an electric constant temperature drying oven, the temperature is set to 80°C, and the hydrothermal reaction is carried out at a constant temperature for 3 hours. After the hydrothermal reaction is completed, the mixture after the hydrothermal reaction is taken out, the temperature is set to 90°C in the oven, the evaporation time is 4 hours, and the glycerol solvent is evaporated. After the evaporation is completed, the obtained solid material is taken out and ground to the required particle size to obtain a silicon / carbon composite material.
[0022] S2, pre-treat chitosan, add the pre-treated chitosan to the silicon / carbon composite material obtained in step S1, mix evenly, cool at a rate of 5°C / min, then add ethylene carbonate to gradually solidify, and obtain the silicon-carbon negative electrode material: pre-treat chitosan, first remove the moisture in chitosan, dry it in an oven, set the temperature to 80°C, set the time to 2 hours, grind the dried chitosan to an average particle size of 50 mesh, put 100g of dried silicon / carbon composite material into a stirring container, and add 30g of pre-treated chitosan. Turn on the stirrer and mix the chitosan and silicon / carbon composite material evenly with low-speed stirring. After mixing evenly, place the stirring container in a cooling device and gradually reduce the temperature. During the cooling process, continue stirring to ensure that the chitosan and silicon / carbon composite material are fully integrated, the temperature of the mixture drops to 10°C, the cooling rate is 5°C / min, and ethylene carbonate is added after cooling. The amount of ethylene carbonate added is 15% of the total mass of the silicon / carbon composite material and chitosan. During the process of adding ethylene carbonate, stirring is maintained to ensure that the mixture is in uniform contact with ethylene carbonate. As the mixture gradually solidifies, stirring is stopped to obtain a silicon-carbon negative electrode precursor material;
[0023] S3, using chemical vapor deposition method, at a temperature of 850°C, using a mixed gas of acetylene and methane to perform carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step S2 for 1 hour to obtain a negative electrode material. This negative electrode material is directly used as a silicon-carbon negative electrode material, and is made into a negative electrode sheet and the electrode sheet is used in a lithium-ion battery.
[0024] Comparative Example 1
[0025] First, amorphous silicon powder and acetylene black are mixed in a ratio of 9:2, and then added to a glycerol solution (the mass of the glycerol solution is about 10 times the total mass of amorphous silicon and acetylene black), and then tin oxide is added, the amount of tin oxide added is 8% of the total mass of amorphous silicon and acetylene black, and ultrasonic dispersion is performed by an ultrasonic disperser for 10 minutes. After ultrasonic dispersion, a tin oxide-amorphous silicon-acetylene black mixture is obtained, and the tin oxide-amorphous silicon-acetylene black mixture is transferred to a magnetic stirrer, polyvinyl pyrrolidone is added, and mechanical stirring is performed, the stirring speed is set to 1000rpm, and the stirring time is about 2 hours, until the mixture becomes viscous. Then it is transferred to an electric constant temperature drying oven, the temperature is set to 80°C, and the hydrothermal reaction is carried out at a constant temperature for 3 hours. After the hydrothermal reaction is completed, the mixture after the hydrothermal reaction is taken out, the temperature is set to 90°C in the oven, the evaporation time is 4 hours, and the glycerol solvent is evaporated. After the evaporation is completed, the obtained solid material is taken out and ground to the required particle size to obtain a silicon / carbon composite material.
[0026] S2, pre-treat chitosan, add the pre-treated chitosan to the silicon / carbon composite material obtained in step S1, mix evenly, cool at a rate of 5°C / min, then add ethylene carbonate to gradually solidify, and obtain the silicon-carbon negative electrode material: pre-treat chitosan, first remove the moisture in chitosan, dry it in an oven, set the temperature to 80°C, set the time to 2 hours, grind the dried chitosan to an average particle size of 50 mesh, put 100g of dried silicon / carbon composite material into a stirring container, and add 30g of pre-treated chitosan. Turn on the stirrer and mix the chitosan and silicon / carbon composite material evenly with low-speed stirring. After mixing evenly, place the stirring container in a cooling device and gradually reduce the temperature. During the cooling process, continue stirring to ensure that the chitosan and silicon / carbon composite material are fully integrated, the temperature of the mixture drops to 10°C, the cooling rate is 5°C / min, and ethylene carbonate is added after cooling. The amount of ethylene carbonate added is 15% of the total mass of the silicon / carbon composite material and chitosan. During the process of adding ethylene carbonate, stirring is maintained to ensure that the mixture is in uniform contact with ethylene carbonate. As the mixture gradually solidifies, stirring is stopped to obtain a silicon-carbon negative electrode precursor material;
[0027] S3, using chemical vapor deposition method, at a temperature of 850°C, using a mixed gas of acetylene and methane to perform carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step S2 for 1 hour to obtain a negative electrode material. This negative electrode material is directly used as a silicon-carbon negative electrode material, and is made into a negative electrode sheet and the electrode sheet is used in a lithium-ion battery.
[0028] Comparative Example 2
[0029] First, amorphous silicon powder and acetylene black are mixed in a ratio of 7:2, and then added to a glycerol solution (the mass of the glycerol solution is about 10 times the total mass of amorphous silicon and acetylene black), and then tin oxide is added, the amount of tin oxide added is 8% of the total mass of amorphous silicon and acetylene black, and ultrasonic dispersion is performed by an ultrasonic disperser for 10 minutes. After ultrasonic dispersion, a tin oxide-amorphous silicon-acetylene black mixture is obtained, and the tin oxide-amorphous silicon-acetylene black mixture is transferred to a magnetic stirrer, polyvinyl pyrrolidone is added, and mechanical stirring is performed, the stirring speed is set to 1000rpm, and the stirring time is about 2 hours, until the mixture becomes viscous. Then it is transferred to an electric constant temperature drying oven, the temperature is set to 80°C, and the constant temperature is used for a hydrothermal reaction for 3 hours. After the hydrothermal reaction is completed, the mixture after the hydrothermal reaction is taken out, the temperature is set to 90°C in the oven, the evaporation time is 4 hours, and the glycerol solvent is evaporated. After the evaporation is completed, the obtained solid material is taken out and ground to the required particle size to obtain a silicon / carbon composite material.
[0030] S2, pre-treat chitosan, add the pre-treated chitosan to the silicon / carbon composite material obtained in step S1, mix evenly, cool at a rate of 5°C / min, then add ethylene carbonate to gradually solidify, and obtain the silicon-carbon negative electrode material: pre-treat chitosan, first remove the moisture in chitosan, dry it in an oven, set the temperature to 80°C, set the time to 2 hours, grind the dried chitosan to an average particle size of 50 mesh, put 100g of dried silicon / carbon composite material into a stirring container, and add 30g of pre-treated chitosan. Turn on the stirrer and mix the chitosan and silicon / carbon composite material evenly with low-speed stirring. After mixing evenly, place the stirring container in a cooling device and gradually reduce the temperature. During the cooling process, continue stirring to ensure that the chitosan and silicon / carbon composite material are fully integrated, the temperature of the mixture drops to 10°C, the cooling rate is 5°C / min, and ethylene carbonate is added after cooling. The amount of ethylene carbonate added is 15% of the total mass of the silicon / carbon composite material and chitosan. During the process of adding ethylene carbonate, stirring is maintained to ensure that the mixture is in uniform contact with ethylene carbonate. As the mixture gradually solidifies, stirring is stopped to obtain a silicon-carbon negative electrode precursor material;
[0031] S3, using chemical vapor deposition method, at a temperature of 850°C, using a mixed gas of acetylene and methane to perform carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step S2 for 1 hour to obtain a negative electrode material. This negative electrode material is directly used as a silicon-carbon negative electrode material, and is made into a negative electrode sheet and the electrode sheet is used in a lithium-ion battery.
[0032] Comparative Example 3
[0033] First, amorphous silicon powder and acetylene black are mixed in a ratio of 8:2, and then added to a glycerol solution (the mass of the glycerol solution is about 10 times the total mass of amorphous silicon and acetylene black), and then tin oxide is added, the amount of tin oxide added is 8% of the total mass of amorphous silicon and acetylene black, and ultrasonic dispersion is performed by an ultrasonic disperser for 10 minutes. After ultrasonic dispersion, a tin oxide-amorphous silicon-acetylene black mixture is obtained, and the tin oxide-amorphous silicon-acetylene black mixture is transferred to a magnetic stirrer, polyvinyl pyrrolidone is added, and mechanical stirring is performed, the stirring speed is set to 1000rpm, and the stirring time is about 2 hours, until the mixture becomes viscous. Then it is transferred to an electric constant temperature drying oven, the temperature is set to 80°C, and the hydrothermal reaction is carried out at a constant temperature for 3 hours. After the hydrothermal reaction is completed, the mixture after the hydrothermal reaction is taken out, the temperature is set to 90°C in the oven, the evaporation time is 4 hours, and the glycerol solvent is evaporated. After the evaporation is completed, the obtained solid material is taken out and ground to the required particle size to obtain a silicon / carbon composite material.
[0034] S2, pre-treat chitosan, add the pre-treated chitosan to the silicon / carbon composite material obtained in step S1, mix evenly, cool at a rate of 5°C / min, then add ethylene carbonate to gradually solidify, and obtain the silicon-carbon negative electrode material: pre-treat chitosan, first remove the moisture in chitosan, dry it in an oven, set the temperature to 80°C, set the time to 2 hours, grind the dried chitosan to an average particle size of 50 mesh, put 100g of dried silicon / carbon composite material into a stirring container, and add 30g of pre-treated chitosan. Turn on the stirrer and mix the chitosan and silicon / carbon composite material evenly with low-speed stirring. After mixing evenly, place the stirring container in a cooling device and gradually reduce the temperature. During the cooling process, continue stirring to ensure that the chitosan and silicon / carbon composite material are fully integrated, the temperature of the mixture drops to 10°C, the cooling rate is 5°C / min, and ethylene carbonate is added after cooling. The amount of ethylene carbonate added is 15% of the total mass of the silicon / carbon composite material and chitosan. During the process of adding ethylene carbonate, keep stirring so that the mixture is evenly in contact with ethylene carbonate. As the mixture gradually solidifies, stop stirring. At this time, the silicon-carbon negative electrode material has been initially formed. The solidified silicon-carbon negative electrode material is taken out and dried to remove excess solvent and moisture. This silicon-carbon negative electrode material is directly used as a silicon-carbon negative electrode material and made into a negative electrode sheet, and the electrode sheet is applied to a lithium-ion battery.
[0035] Comparative Example 4
[0036] First, amorphous silicon powder and acetylene black are mixed in a ratio of 8:2, and then added to a glycerol solution (the mass of the glycerol solution is about 10 times the total mass of amorphous silicon and acetylene black), and then tin oxide is added, the amount of tin oxide added is 8% of the total mass of amorphous silicon and acetylene black, and ultrasonic dispersion is performed by an ultrasonic disperser for 10 minutes. After ultrasonic dispersion, a tin oxide-amorphous silicon-acetylene black mixture is obtained, and the tin oxide-amorphous silicon-acetylene black mixture is transferred to a magnetic stirrer, polyvinyl pyrrolidone is added, and mechanical stirring is performed, the stirring speed is set to 1000rpm, and the stirring time is about 2 hours, until the mixture becomes viscous. Then it is transferred to an electric constant temperature drying oven, the temperature is set to 80°C, and the hydrothermal reaction is carried out at a constant temperature for 3 hours. After the hydrothermal reaction is completed, the mixture after the hydrothermal reaction is taken out, the temperature is set to 90°C in the oven, the evaporation time is 4 hours, and the glycerol solvent is evaporated. After the evaporation is completed, the obtained solid material is taken out and ground to the required particle size to obtain a silicon / carbon composite material.
[0037] S2, adding ethylene carbonate to the silicon / carbon composite material obtained in step S1 until it gradually solidifies, and in the process of adding ethylene carbonate, stirring is maintained to make the silicon / carbon composite material uniformly contact with ethylene carbonate. As the mixture gradually solidifies, stirring is stopped to obtain a silicon-carbon negative electrode precursor material;
[0038] S3, using chemical vapor deposition method, at a temperature of 850°C, using a mixed gas of acetylene and methane to perform carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step S2 for 1 hour to obtain a negative electrode material. This negative electrode material is directly used as a silicon-carbon negative electrode material, and is made into a negative electrode sheet and the electrode sheet is used in a lithium-ion battery.
[0039] Comparative Example 5
[0040] First, amorphous silicon powder and acetylene black are mixed in a ratio of 8:2, and then added to a glycerol solution (the mass of the glycerol solution is about 10 times the total mass of amorphous silicon and acetylene black), and ultrasonically dispersed for 10 minutes by an ultrasonic disperser to obtain an amorphous silicon-acetylene black mixture, and the amorphous silicon-acetylene black mixture is transferred to a magnetic stirrer, polyvinyl pyrrolidone is added, and mechanical stirring is performed, the stirring speed is set to 1000rpm, and the stirring time is about 2 hours, until the mixture becomes viscous. Then it is transferred to an electric constant temperature drying oven, the temperature is set to 80°C, and the hydrothermal reaction is carried out at a constant temperature for 3 hours. After the hydrothermal reaction is completed, the mixture after the hydrothermal reaction is taken out, the temperature is set to 90°C in the oven, the evaporation time is 4 hours, and the glycerol solvent is evaporated. After the evaporation is completed, the obtained solid material is taken out and ground to the desired particle size to obtain a silicon / carbon composite material.
[0041] S2, pre-treat chitosan, add the pre-treated chitosan to the silicon / carbon composite material obtained in step S1, mix evenly, cool at a rate of 5°C / min, then add ethylene carbonate to gradually solidify, and obtain the silicon-carbon negative electrode material: pre-treat chitosan, first remove the moisture in chitosan, dry it in an oven, set the temperature to 80°C, set the time to 2 hours, grind the dried chitosan to an average particle size of 50 mesh, put 100g of dried silicon / carbon composite material into a stirring container, and add 30g of pre-treated chitosan. Turn on the stirrer and mix the chitosan and silicon / carbon composite material evenly with low-speed stirring. After mixing evenly, place the stirring container in a cooling device and gradually reduce the temperature. During the cooling process, continue stirring to ensure that the chitosan and silicon / carbon composite material are fully integrated, the temperature of the mixture drops to 10°C, the cooling rate is 5°C / min, and ethylene carbonate is added after cooling. The amount of ethylene carbonate added is 15% of the total mass of the silicon / carbon composite material and chitosan. During the process of adding ethylene carbonate, stirring is maintained to ensure that the mixture is in uniform contact with ethylene carbonate. As the mixture gradually solidifies, stirring is stopped to obtain a silicon-carbon negative electrode precursor material;
[0042] S3, using chemical vapor deposition method, at a temperature of 850°C, using a mixed gas of acetylene and methane to perform carbon coating treatment on the silicon-carbon negative electrode precursor material obtained in step S2 for 1 hour to obtain a negative electrode material. This negative electrode material is directly used as a silicon-carbon negative electrode material, and is made into a negative electrode sheet and the electrode sheet is used in a lithium-ion battery.
[0043] The performance test was performed on the lithium electronic batteries of Example 1 and Comparative Examples 1-5, and the specific test method is as follows:
[0044] Constant current charge and discharge test
[0045] The LANDCT2001A battery testing system was used to perform constant current charge and discharge tests on the button batteries packaged in the embodiments and comparative examples. The charge and discharge mode was as follows: the battery was first discharged to 0.02V at a constant current (0.15mA), then allowed to stand for 1min and then charged to 1.5V at a constant current (0.15mA).
[0046] Capacity decay rate test
[0047] Using LANDCT2001A battery testing system, the packaged batteries of the embodiments and comparative examples were subjected to charge and discharge tests at a constant temperature, and the initial capacity of each sample was recorded. Afterwards, 50 charge and discharge cycles were performed, and the final current capacity was recorded. Capacity decay rate = (initial capacity - current capacity) / initial capacity × 100%.
[0048] Table 1 Constant current charge and discharge test results
[0049] project <![CDATA[Initial charging specific capacity (mAhg -1 )]]> Example 1 589.5 Comparative Example 1 440.1 Comparative Example 2 429.6 Comparative Example 3 350.4 Comparative Example 4 340.5 Comparative Example 5 333.9
[0050] Table 2 Capacity attenuation rate test results
[0051]
[0052]
[0053] It can be seen from Tables 1-2 that the first-cycle charging specific capacity of the low expansion rate silicon-carbon negative electrode material prepared in Example 1 is higher than the first-cycle charging specific capacity of the low expansion rate silicon-carbon negative electrode material prepared in Comparative Examples 1-5. It can be seen from Table 2 that the capacity attenuation rate of the low expansion rate silicon-carbon negative electrode material prepared in Example 1 is lower than the capacity attenuation rate of the low expansion rate silicon-carbon negative electrode material prepared in Comparative Examples 1-5. This is because the amount of amorphous silicon and acetylene black is controlled during the preparation process of the embodiment. At the same time, the addition of chitin forms a certain pore structure in the silicon-carbon composite material, which helps to increase the specific surface area of the material, thereby improving its electrochemical performance.
[0054] Therefore, the present application provides a silicon-carbon negative electrode material with a low expansion rate and a preparation method and application thereof, which solves the problems of large volume expansion rate and poor cycle capacity in the prior art.
[0055] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.
[0056] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a silicon-carbon negative electrode material with a low expansion rate, characterized in that: The method comprises the following preparation steps: S1. Amorphous silicon and acetylene black are mixed in a glycerol solution, and then tin oxide is added to obtain a tin oxide-amorphous silicon-acetylene black mixture after ultrasonic dispersion. Polyvinyl pyrrolidone solution is added to the obtained tin oxide-amorphous silicon-acetylene black mixture, and the mixture is mechanically stirred to be uniform. A hydrothermal reaction is carried out at a constant temperature in an electric constant temperature drying oven, the glycerol solvent is evaporated, and the silicon / carbon composite material is obtained by grinding. S2, adding chitosan to the silicon / carbon composite material obtained in step S1, mixing evenly, cooling the mixture, and then adding ethylene carbonate to gradually solidify the mixture to obtain a silicon-carbon negative electrode precursor material; S3, carbon-coating the silicon-carbon negative electrode precursor material obtained in step S2 by chemical vapor deposition to obtain a carbon-coated silicon-carbon negative electrode material.
2. The method for preparing a silicon-carbon negative electrode material with a low expansion coefficient according to claim 1, characterized in that: In step S1, the mass ratio of amorphous silicon to acetylene black is 8:2, the amount of tin oxide added is 8% of the total mass of amorphous silicon and acetylene black, the amount of polyvinyl pyrrolidone added is 5% of the mass of the tin oxide-amorphous silicon-acetylene black mixture, and the mass of the glycerol solution is 10 times the total mass of amorphous silicon and acetylene black.
3. The method for preparing a silicon-carbon negative electrode material with a low expansion coefficient according to claim 1, characterized in that: In the step S2, the mass ratio of the silicon / carbon composite material to chitosan is 10:3, and the amount of ethylene carbonate added is 15% of the total mass of the silicon / carbon composite material and chitosan.
4. The method for preparing a silicon-carbon negative electrode material with a low expansion coefficient according to claim 1, characterized in that: In the step S1, the mechanical stirring time is 2 hours, the mechanical stirring speed is 1000 rpm, the temperature of the electric thermostat is 80° C., and the hydrothermal reaction time is 3 hours.
5. The method for preparing a silicon-carbon negative electrode material with a low expansion coefficient according to claim 1, characterized in that: In the step S1, evaporation of the glycerol solvent is performed in an oven at a temperature of 90° C. for 4 hours.
6. The method for preparing a silicon-carbon negative electrode material with a low expansion coefficient according to claim 4, characterized in that: In the step S2, before chitosan is added to the silicon / carbon composite material obtained in step S1 and mixed evenly, the chitosan is dried in an oven and then ground to a particle size of 50 meshes.
7. The method for preparing a silicon-carbon negative electrode material with a low expansion coefficient according to claim 4, characterized in that: In step S2, the temperature is lowered to 10°C at a rate of 5°C / min.
8. The method for preparing a silicon-carbon negative electrode material with a low expansion coefficient according to claim 7, characterized in that: In step S3, the temperature of carbon coating is 850-900°C, the gas source used is acetylene, methane, liquefied gas or gaseous carbon source, and the duration is 1 hour.
9. The silicon-carbon negative electrode material obtained according to the method for preparing a silicon-carbon negative electrode material with a low expansion coefficient according to any one of claims 1 to 8.
10. Application of the silicon-carbon negative electrode material obtained by the method for preparing a silicon-carbon negative electrode material with a low expansion coefficient according to claim 9 in a lithium battery.
Citation Information
Patent Citations
Preparation method of silicon-carbon negative electrode material with low expansion rate as well as product and application of silicon-carbon negative electrode material
CN118039834A
Method for Converting Carbon Dioxide (CO2) into CO by an Electrolysis Reaction
US20220056602A1
